An athletic director's story and the future of college sports in America - Mulcahy, Robert E.; Stewart, Robert, 1949- (Rutgers University Press, 2020)
"Robert Mulcahy's chronicle of his decade leading Rutgers University athletics is an intriguing story about fulfilling a vision. The goal was to expand pride in intercollegiate athletics. Redirecting a program with clearer direction and strategic purpose brought encouraging results. Advocating for finer coaching and improved facilities, he and Rutgers achieved national honors in Division I sports. Unprecedented alumni interest and support for athletics swelled across the Rutgers community. Though Mr. Mulcahy left Rutgers in 2009, his memoir reflects continued devotion to intercollegiate athletics and student athletes. His insights for addressing several leading issues confronting Division I sports today offer guidelines for present and future athletic directors to follow"--